2021
DOI: 10.3390/foods10071501
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Fermented with Kimchi-Derived Lactic Acid Bacteria Prevents Metabolic Complications in Mice on a High-Fat and -Cholesterol Diet

Abstract: This aim of this study was to investigate the potential beneficial effects of rice bran powder, fermented by Weissella koreensis DB1 isolated from kimchi, to protect against obesity and dyslipidemia induced by a high-fat and high-cholesterol diet, in a mouse model. Male mice were fed a modified AIN-93M diet containing high fat/high-cholesterol (HFCD), or same diet supplemented with non-fermented rice bran powder (HFCD-RB) or fermented rice bran powder (HFCD-FRB) for 10 weeks. In the HFCD-FRB group, body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 80 publications
0
8
0
2
Order By: Relevance
“…Lipid accumulation was also improved by FRB treatment in IR-HepG2 cells [ 35 ]. In a mouse model of obesity, it was reported that supplementation with FRB could decrease fatty depositions in liver tissues [ 36 ]. Another study showed that the inflammatory reactions were inhibited after FRB treatment by suppressing the mRNA levels of TNF-α and IL-6 in RBL-2H3 cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid accumulation was also improved by FRB treatment in IR-HepG2 cells [ 35 ]. In a mouse model of obesity, it was reported that supplementation with FRB could decrease fatty depositions in liver tissues [ 36 ]. Another study showed that the inflammatory reactions were inhibited after FRB treatment by suppressing the mRNA levels of TNF-α and IL-6 in RBL-2H3 cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was pointed out that hypoadiponectinemia and higher levels of serum leptin commonly occurred in NASH patients [ 9 ]. Increased serum leptin levels and decreased serum adiponectin levels were also observed in mice fed a HF diet for 10 weeks [ 36 ]. In addition, SIRT1 and AMPK were indicated to suppress lipogenesis through inhibition of SREBP-1 levels and also activation of FA oxidation via PPARα in the liver [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermented products, which provided live microbial, have been commonly applied in the human and poultry industry (Li et al, 2020 ; Park et al, 2021 ; Wu et al, 2021 ; Lv et al, 2022 ). Rice bran fermented by Weissella koreensis DB1 can decrease the serum levels of triglyceride (TG) and total cholesterol (TC) and significantly downregulate the hepatic gene expression of C/EBP, SREBP-1c, FAS, and ACC in mice (Park et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fermented products, which provided live microbial, have been commonly applied in the human and poultry industry (Li et al, 2020 ; Park et al, 2021 ; Wu et al, 2021 ; Lv et al, 2022 ). Rice bran fermented by Weissella koreensis DB1 can decrease the serum levels of triglyceride (TG) and total cholesterol (TC) and significantly downregulate the hepatic gene expression of C/EBP, SREBP-1c, FAS, and ACC in mice (Park et al, 2021 ). Meanwhile, many in vitro fermentation studies have shown that fermented feed can improve poultry egg performance, immune function, intestinal development, and lipid metabolism (Engberg et al, 2009 ; Gao et al, 2009 ; Olukomaiya et al, 2019 ; Sugiharto and Ranjitkar, 2019 ; Saleh et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%